Interpreting T-bar tests in ultra-soft clay - Sahdi, F.; Gaudin, C.; Boylan, N. (ICE Publishing, 2014)
This technical note describes a simple methodology for reliably measuring the undrained strength of ultra-soft consolidating clay in the geotechnical centrifuge, using the T-bar penetrometer. This methodology relies on the T-bar resistance force owing to soil strength being equal, albeit in the opposite direction, during penetration and extraction when the soil is fully remoulded. The other components of resistance from soil buoyancy, bar self-weight and soil lateral pressure on the T-bar axial strain gauge act in the same direction regardless of the direction of bar movement. The method uses cycles of penetration and extraction to determine the correction required to eliminate these effects. The methodology was validated by comparing the strength inferred from 81 T-bar penetrometer tests with a large strain numerical simulation of consolidation and the resulting gain in soil strength.